First case report of cerebral folate deficiency caused by a novel mutation of FOLR1 gene in a Chinese patient - Ciliu Zhang; Xiaolu Deng; Yafei Wen; Fang He; Fei Yin; Jing Peng (BMC, 2020)
Abstract Background Cerebral folate deficiency (CFD) is a neurological disease, hallmarked by remarkable low concentrations of 5-methyltetrahydrofolic acid (5-MTHF) in cerebrospinal fluid (CSF). The primary causes of CFD include the presence of folate receptor (FR) autoantibodies, defects of FR encoding gene FOLR1, mitochondrial diseases and congenital abnormalities in folate metabolism. Case presentation Here we first present a Chinese male CFD patient whose seizure onset at 2 years old with convulsive status epilepticus. Magnetic Resonance Imaging (MRI) revealed the development of encephalomalacia, laminar necrosis in multiple lobes of the brain and cerebellar atrophy. Whole Exome Sequencing (WES) uncovered a homozygous missense variant of c.524G > T (p.C175F) in FOLR1 gene. Further laboratory tests demonstrated the extremely low level of 5-MTHF in the CSF from this patient, which was attributed to cerebral folate transport deficiency. Following the intravenous and oral treatment of calcium folinate, the concentrations of 5-MTHF in CSF were recovered to the normal range and seizure symptoms were relieved as well. Conclusions One novel variation of FOLR1 was firstly identified from a Chinese male patient with tonic-clonic seizures, developmental delay, and ataxia. The WES and laboratory results elucidated the etiology of the symptoms. Clinical outcomes were improved by early diagnosis and proper treatment.